Absence of Transgenerational Phenotypic Plasticity in Fecundity in the Parasitoid Anagrus erythroneurae (Hymenoptera: Mymaridae). Issue 1 (30th September 2015) - Andreazza, Felipe; Rosenheim, Jay A.
Abstract : To improve biological pest control, we would like to understand the main factors that limit the reproductive success of key biological control agents, including parasitoid wasps. Previous research with proovigenic parasitoids in the genus Anagrus collected from multiple field sites revealed positive correlations between parasitoid fecundity and local host density. In this article, we test whether this variation in fecundity is a reflection of transgenerational phenotypic plasticity. We exposed females in laboratory microcosms to either low or high host densities and then quantified the fecundity of their adult daughters. Mean fecundity of daughters did not differ across host density treatments, arguing against the operation of phenotypic plasticity. Significant variation in mean fecundity across different families instead suggested the possibility that genetic variation may underlie the observed fecundity differences.